Milan System for Reporting Salivary Gland Cytopathology– An Experience from Western Indian Population - Gaikwad, Vaishali P (J Cytol, 2020)
INTRODUCTION: Fine-needle aspiration cytology (FNAC) can be challenging to provide a precise diagnosis in salivary gland cytopathology due to diversity of lesions and cytomorphological convergence between the tumors and within the same tumor of salivary gland. The recently proposed Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) provides a risk stratification-based classification system with an intrinsic risk of malignancy (ROM) for each diagnostic category, which aims to furnish useful information to the clinicians. This study was undertaken to evaluate the diagnostic utility and validity of MSRSGC. METHODS AND MATERIAL: In this retrospective study, FNAC done for all salivary gland lesions over a period of two years were retrieved. All cases were categorized according to MSRSGC and correlated with histopathological follow-up, wherever available. ROM was calculated for each category. RESULTS: The cases belong to following categories: non-diagnostic (1.27%), non-neoplastic (30.38%), atypia of undetermined significance (5.06%), benign neoplasm (46.84%), salivary gland neoplasm of uncertain malignant potential (1.27%), suspicious for malignancy (1.27%), and malignant (13.92%). Out of 79 cases, 50.63% had follow-up. The ROM were 0% for category II and IVa, 50% for category III, and 100% for category IVb, V, and VI. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were recorded as 77.78%, 100%, 100%, 91.3%, and 93.33%, respectively. CONCLUSIONS: Application of MSRSGC has immense value for standardization of reporting of salivary gland FNAC. Our data corresponds to the studies done worldwide and recommends the use of MSRSGC for future diagnostic purposes.